Patterns of Perceptions towards the Anticorruption Fight and Policies in Romania. Balancing between Façade and Essence - Precupeţu, Iuliana (Calitatea Vieții, 2009)
The paper describes the models of perception towards the anticorruption fight and policies in Romania. Using a Grounded Theory approach, the article highlights the main themes in regard to efforts of curbing corruption. The data consisted from documents on the topic of corruption and interviews with experts, covering the period 2001-2007. Taking into consideration the position expressed by six important target-groups with major roles in combating corruption (economy, politics, civil society, media, police and judiciary), the paper presents a model that emerged from qualitative analysis of data. The model highlights the assessments of fight against corruption, the barriers identified in the anticorruption efforts, the general orientation and directions of fight against the phenomenon. The description of perceptions proves that corruption remains a very controversial issue, while in regard to anticorruption fight it is obvious from the analysis a certain pondering of perceptions between considering the fight as substantial, targeting the very core of the phenomenon and deeming the fight as only a spurious effort that will not affect seriously corruption, in the long term.